Legal Analysis of Legal Protection for Landowner Farmers Against Investor Domination in Agrarian Policy in Indonesia - Surya Asman Jaya; Herlita Eryke (UNIVERSITAS PAKUAN, 2026)
The issue of legal protection for landowner farmers in their interactions with investors and government bias is a critical topic in economic development and land management in Indonesia. This study aims to analyze existing legal protections for landowner farmers against investors and to evaluate how government bias is reflected in current agrarian policies. This research uses a qualitative approach, drawing on literature and analyzing relevant laws, regulations, and secondary data. The results show that although Indonesia has a legal framework, such as the Basic Agrarian Law (UUPA) No. 5 of 1960, to ensure fair land distribution, its implementation is often ineffective due to economic inequality and limited legal knowledge among farmers. In addition, the findings show that many land agreements involving farmers lack transparency, making them vulnerable to disadvantageous contracts and land conversion. Analysis shows that the imbalance of power between farmers and large-scale investors often leads to injustice, as economic interests often override the protection of agrarian rights. Although programs such as Agrarian Reform exist, they face significant bureaucratic and administrative obstacles that hinder the redistribution of land to those who need it. As a result, the government's role is often seen as favoring industrial interests, such as large plantations, over the welfare of small-scale farmers. Based on these findings, it is recommended that the government strengthen agrarian reform mechanisms by improving data validation and simplifying administrative procedures. In addition, providing legal education and assistance to farmers is essential to raise their legal awareness and prevent them from entering into disadvantageous agreements.